Unveiling the Shadows: The Tactics of Social Media Platforms on Human Trafficking in Mbeya, Tanzania - Kulyakwave, Peter David; Rwabishugi, Leticia Lucas; Kulyakwave, Linda (International Journal of Conflict Management, 2025)
This paper aims to explore the tactics that the traffickers use on the media platforms in the Mbeya Region of Tanzania. The analysis involved 35 respondents, including victims, community leaders and law enforcers. The study used the descriptive research design whereby questionnaires were developed and used in data collection. The results indicated that the most often used social media platforms were Facebook (40%) and WhatsApp (30%), while Instagram ranked third with 20% and the last was Telegram (10%). The majority of the affected respondents were young women ages 18-24 years making up 50% of the participants. This article identified emotional manipulation, social proof, and fake job offers as the most common recruitment strategies. The outcomes reveal the critical need for strategic approaches and community awareness in combating the enabled trafficking by the use of social media.